Rowing distance-speed-rate calculator (BioRow, 2015)
The Rowing Distance-Speed-Rate Calculator ist presented. Contents: - datainput (race distance and time) - calculation of time, speed, distance, trend, - training speeds & stroke rates (intensities) at various distances, - training speeds & stroke rates (intensities) at various durations of exercise, - training speeds at different stroke rates and distances.